Recovery From a Forward Falling Slip: Measurement of Dynamic Stability and Strength Requirements Using a Split-Belt Instrumented Treadmill - Debelle, Héloïse; Harkness-Armstrong, Carla; Hadwin, Kathryn; Maganaris, Constantinos N.; O'Brien, Thomas D. (Frontiers in Sports and Active Living, 2020)
Aim: Falls commonly occur from trips and slips while walking. Recovery strategies from trips and backward falling slips have been extensively studied. However, until recently, forward falling slips (FFSs) have been considered less dangerous and have been understudied. This study aimed first to create an application to realistically simulate FFSs using a split-belt instrumented treadmill and then to understand the biomechanical requirements for young adults to recover from an FFS. Methods: We developed a semi-automatic custom-made application on D-Flow that triggered FFSs by briefly and unexpectedly increasing the speed (a = 5 m·s−2) of the right belt during stance. To validate the protocol, we tested against criteria defined for an ecologically and experimentally valid FFS: unexpected occurrence of the slip, increased foot velocity, forward loss of balance during the slip and consistent perturbation timing. We evaluated the recovery strategies of 17 young adults by measuring dynamic stability, joint moments and ground reaction force (GRF) vector angles before, during and on 15 steps following the FFS. Results: The application successfully triggered FFSs, according to the criteria we defined. Participants' balance returned to normal for a minimum of three consecutive steps in 10.9 (7.0) steps. Recovery from the FFSs was characterised by larger hip flexor and knee extensor moments to support the centre of mass during the slip, and a longer first recovery step with large hip extensor moments to arrest the fall followed by large knee extensor moments to raise and advance the centre of mass into the next step (p < 0.001 compared with normal gait). Subsequent steps progressively returned to normal. Conclusion: This is the first study to experimentally simulate FFSs meeting the aforementioned criteria, and to measure their effects on the dynamic balance and kinetic parameters. The split-belt instrumented treadmill proved a promising tool to better study the mechanisms of falls and recovery. The required large hip and knee joint moments generally agree with findings on trips and backward falling slips and provide an indication of the functional capacities that should be targeted in fall-prevention interventions. These findings should be used to better understand and target the mechanisms of balance loss and falls in older adults following FFSs.